Elucidating the relationship between crystallo-chemistry and optical properties of CIGS nanocrystals. (20th December 2016) - Ahmadi, Mahshid; Pramana, Stevin S; Boothroyd, Chris; Lam, Yeng Ming
Abstract: The performance of solar cells fabricated using Cu(In, Ga)(S, Se)2 nanocrystal (NC) inks synthesized using the hot injection method has yielded efficiencies up to 12% recently. The efficiency of these devices is highly dependent on the chemical composition and crystallographic quality of the NCs. The former has been extensively discussed as it can be easily correlated to the optical properties of the film, but detailed crystallographic structure of these NCs has scarcely been discussed and it can influence both the optical and electrical properties. Hence both chemical composition and crystal structure should be explored for these NCs in order for this material to be further developed for application in thin film solar cells. In this work, a thorough investigation of the composition and crystal structure of CuIn x Ga1− x Se2 NCs synthesized using the hot injection method over the entire composition range (0 ≤ x ≤ 1) has been conducted. Raman spectroscopy of the NCs complements the information derived from x-ray diffraction (XRD) and electron probe microanalysis (EPMA). EPMA, which was carried out for the first time, indicates good controllability of the NC Ga/(In + Ga) ratio using this synthesis method. Raman spectroscopy reveals that CuInSe2 NCs are a mixture of chalcopyrite and sphalerite with disordered cations, whereas CuGaSe2 NCs are purely chalcopyrite. The lattice parameters determined from XRD were found to deviate from those calculated using Vegard's law for all compositions. Hence, it can be deduced that the lattice is distorted in the crystal. The optical and electrochemical band gap of CuIn x Ga1− x Se2 NCs increases as the Ga content increases. The energy band gap deviates from the theoretical values, which could be related to the contribution from cation disordering and strain. These results help to tailor the opto-electrical properties of semiconductors, which inherently depend on the crystalline quality, strain and composition.